Bronze Age tell communities in context, Part 2: Practice - The social, space, and materiality an exploration into culture, society and the study of European prehistory - Kienlin, Tobias L. (Archaeopress Publishing Ltd, 2020)
This study challenges current modelling of Bronze Age tell communities in the Carpathian Basin in terms of the evolution of functionally-differentiated, hierarchical or 'proto-urban' society under the influence of Mediterranean palatial centres
Includes bibliographical references
Keywords: Bronze age / Europe; Bronzezeit; Wohnhügel; Europa